2018
DOI: 10.1080/20964129.2018.1532772
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen enrichment alters carbon fluxes in a New England salt marsh

Abstract: Introduction: Nitrogen enrichment of coastal salt marshes can induce feedbacks that alter ecosystem-level processes including primary production and carbon sequestration. Despite the rising interest in coastal blue carbon, the effects of chronic nutrient enrichment on blue carbon processes have rarely been measured in the context of experimental fertilization. Here, we examined the ecosystem-level effects of nitrate (NO 3 −) enrichment on the greenhouse gas dynamics of a Spartina alterniflora-dominated salt ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Therefore, in all cases when NO3− was directly added to marsh sediments, both to the rhizosphere and to the overlying water in intact cores, there was a rapid increase in microbial respiration of NO3− through denitrification. In situ measurements of ecosystem respiration (Geoghegan et al 2018 ) and soil respiration (Wigand et al 2018 ) were also significantly higher in the nutrient enriched creeks, providing further evidence of NO3− stimulated microbial processes. This suggests that salt marsh sediments have populations of microbes capable of using NO3− within hours of it being added and implies that there is a sufficient supply of biologically available salt marsh organic matter to support this NO3− respiration.…”
Section: Both Field and Controlled Laboratory Experiments Support Micmentioning
confidence: 90%
“…Therefore, in all cases when NO3− was directly added to marsh sediments, both to the rhizosphere and to the overlying water in intact cores, there was a rapid increase in microbial respiration of NO3− through denitrification. In situ measurements of ecosystem respiration (Geoghegan et al 2018 ) and soil respiration (Wigand et al 2018 ) were also significantly higher in the nutrient enriched creeks, providing further evidence of NO3− stimulated microbial processes. This suggests that salt marsh sediments have populations of microbes capable of using NO3− within hours of it being added and implies that there is a sufficient supply of biologically available salt marsh organic matter to support this NO3− respiration.…”
Section: Both Field and Controlled Laboratory Experiments Support Micmentioning
confidence: 90%
“…This loss of 62 mol C m −2 year −1 along the fertilized edge is significant and could result in a decrease in overall accretion rates and elevation. Other salt marsh studies have similarly concluded that fertilization increases both GPP and R (Anisfeld & Hill, 2012;Caplan et al, 2015;Geoghegan et al, 2018;Martin et al, 2018;Morris & Bradley, 1999;Wang, Zhu et al, 2013); however, studies are less congruent about the effect of fertilization on NEE, showing variation between no detectable effect (Geoghegan et al, 2018) and increasing CO 2 emissions (Caplan et al, 2015;Wang, Zhu et al, 2013). A decrease in soil carbon content has been observed with fertilization (Morris & Bradley, 1999) but may be a result of increased sediment input changing sediment composition rather than loss of carbon in sediment (Morris et al, 2002).…”
Section: Vertical Carbon Fluxes 431 Metabolic Ratesmentioning
confidence: 95%
“…BGB has been observed to either increase (Morris et al, 2013;Wigand et al, 2015) or decrease (Darby & Turner, 2008;Deegan et al, 2012) in response to fertilization. Several studies found that R and GPP (Wigand et al, 2009;Anisfeld & Hill, 2012;Caplan et al, 2015;Geoghegan et al, 2018;Morris & Bradley, 1999;Wang, Zhu et al, 2013, Bulseco et al, 2019 increased in response to fertilization, but the results for NEE were mixed with either no detectable response (Geoghegan et al, 2018) or an increase in net CO 2 emissions (Caplan et al, 2015;Wang, Zhu, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Czapla et al in a companion paper in this issue pointed out that fertilization effects on C fluxes differ across marsh sites due to location‐specific physical and chemical characteristics, and this heterogeneity in responses to fertilization may complicate the relationship between salt marsh N availability and NECB. While several studies have reported an increase in AGB and net CO 2 emissions with fertilization, other studies have reported no effect on AGB (Davis et al, 2017; Johnson et al, 2016) and NEE (Geoghegan et al, 2018) at certain sites. Belowground biomass (BGB) has been reported to either increase (Morris, Sundberg, & Hopkinson, 2013; Wigand et al, 2014), decrease (Darby & Turner, 2008; Deegan et al, 2012; Graham & Mendelsshon, 2016), or remain the same (Davis et al, 2017) in response to fertilization.…”
Section: Introductionmentioning
confidence: 96%